EU INITIATIVES AND PROJECTS IN THE FIELD OF DEFENCE AND SECURITY - Ivasechko, Olha; Zavada, Yaryna (Current Problems of Sustainable Development, 2026)
The issue of security cooperation between the European Union and Ukraine in the context of full-scale Russian aggression has acquired particular importance and it is clearly evident that after 2022 the interaction between the parties has reached a qualitatively new level, transforming into a strategic partnership that has covered the military, political, financial and defense-industrial spheres. The EU is introducing new initiatives such as the European Defense White Paper “Readiness 2030” and the “Rearmament of Europe” plan, which are quite capable of forming a new security architecture of the continent. The authors reveal in the article the role of key mechanisms and instruments, including the Common Security and Defense Policy (CSDP), Permanent Structured Cooperation (PESCO), the European Defense Fund (EDF) and the European Peace Facility (EPF). The practical aspects of cooperation were analyzed, namely the activities of the EUAM Ukraine and EUMAM missions, which ensure security sector reform and training of the Ukrainian military. Particular attention was paid to outlining the significance of new initiatives, such as BraveTech EU, SAFE, EDIP and AGILE, which are aimed at integrating Ukraine into the European defense-industrial base and developing innovative technologies. In the article, the authors emphasize that Ukraine is not only a recipient of assistance, but also an active partner that makes a significant contribution to European security thanks to its own combat experience and potential. At the same time, the main challenges of cooperation were identified, in particular the need to overcome hybrid threats, strengthen coordination of actions and ensure stable financing. At the same time, the article emphasizes that further deepening cooperation requires not only political will, but also institutional coherence between the EU Member States and Ukraine, in particular in matters of standardization, joint production of weapons and integration of defense markets. The authors conclude that the effectiveness of a security partnership largely depends on the ability of the parties to adapt to new geopolitical challenges through unity of approach and coherence of action.